The Implications of Trade War on Multinational Companies: A Study Case Starbucks Expansion in China 2018-2020 - Dyza Rizki Ananda; Bambang Wahyu Nugroho (Social Sciences Journal, 2026)
This study aims to explain in detail the implications of the trade war on multinational companies with a case study of Starbucks expansion in China. The background behind the outbreak of the trade war itself stems from the United States accusing China of illegal practices stealing intellectual property and the United States' growing trade deficit. The trade war by the United States with the imposition of tariffs on several imported products, aims to protect domestic industries and increase employment. However, compared to the benefits, the trade war actually has a negative impact on US industry, both at home and abroad, especially for companies investing in China. Most of the industrial sectors affected are the manufacturing sector, while Starbucks is a multinational company in the food & beverage retail sector. Thus, this study will show that not all companies or industries will be affected by the trade war phenomenon, one of which is Starbucks.